Using aspect-based sentiment analysis to evaluate the global effects of the food security crisis during the Russia-Ukraine war - Aygun, Osman; Aygun, Irfan; Kaya, Mehmet (Elsevier, 2025)
The war that broke out between Russia and Ukraine in February 2022 has left many countries facing difficult challenges, one of which has been the escalation of global food security issues. This study examines how the conditions of war negatively reflect on food security and how social media posts collected from different countries around the world were used to categorize and examine societal concerns following the war. Concerns and reasons were analyzed based on countries using an aspect-based sentiment analysis using a sentiment classifier with the BERT architecture. In Africa and the Middle East, societal concerns are centered around the possibility of not accessing food and potential famine; other analyses conducted in these countries indicate that access to products such as bread, baby food, animal products (milk, cheese, etc.), pasta, and many other categories have become significantly challenging. A large portion of the world views the food security crisis caused by the war as potentially leading to economic problems and famine. Social media posts from Poland, especially, in Central and Eastern European countries are intensely focused on economic issues. The sentiment analysis studies show that the Black Sea Grain Initiative, aimed at securing food security between the two countries, increased positive sentiments globally by up to 24%. To the best of our knowledge, this study is the first to identify concerns stated at the societal level worldwide on food security and measure objectives by country. This study presents findings that can develop projections for assessing concerns reflected in society regarding food security and formulating alternative plans, contributing to many countries in this regard.
Keywords: Aspect based sentiment analysis; Food security; Russia-Ukraine conflict; Wheat crisis; Deep learning